The Main Directions of Improving the Activity of Internal Affairs Bodies of the Republic of Kazakhstan in the Field of Environmental Safety Protection - BAGISOV, N. B. (Journal of Advanced Research in Law and Economics, 2018)
The present article studies the legal fundamentals of the organization and activity of internal affairs bodies aimed at ensuring environmental safety protection in the Republic of Kazakhstan. Despite the expressed increased attention of the scientific community to the environmental safety of the society and the state, currently there is a lack of studies dedicated to the complex analysis of legal protection of the environment, as well as the special analysis of the environmental protection activity of internal affairs bodies. The objective of this work is to reveal the peculiarities of functions of internal affairs bodies of the Republic of Kazakhstan for environmental safety protection. Basing upon the analysis of the current legislation, the forms of independent activity and interaction of the police with other law enforcement agencies are distinguished in the field of implementation of the environmental safety protection function of the state. The article considers the procedural and institutional and prompt measures in the field of counteracting environmental crimes. The article studies the international experience of environmental safety protection by the police: the structure and legal consolidation of their activity; the mechanisms of implementation of the environmental function; the determination of their place and role in the environmental field. The authors draw a conclusionthat the current legislation of the Republic of Kazakhstan does not clearly determine the environmental protection functions of internal affairs bodies; the legislative specification of the environmental safety protection activity of internal affairs bodies is estimated and the idea of the development of a special subdivision of the environmental police is supported.